2020
DOI: 10.1177/0003489420916207
|View full text |Cite
|
Sign up to set email alerts
|

Hemi-laryngopharyngeal Spasm (HeLPS): Defining a New Clinical Entity

Abstract: Objective: Hemi-laryngopharyngeal spasm (HeLPS) has recently been described in the neurosurgical literature as a cause of intermittent laryngopharyngeal spasm and cough due to vascular compression of the vagus nerve at the cerebellopontine angle. We present the diagnostic criteria for this syndrome. Methods: A retrospective chart review of six patients with HeLPS and three patients misdiagnosed with this condition are presented. All patients were diagnosed and treated at a tertiary care academic centre from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Previous cases of HeLPS treated using neurosurgery are listed in Table . Only 6 such cases were treated with MVD; symptoms were relieved in all cases although transient vagus nerve palsy occurred in 3 cases. [4][5][6][7][8] Preoperatively, 4 of the 6 reported patients were taken to the emergency department and 2 were admitted to the intensive care unit. One patient was intubated for respiratory distress and stridor; the other required a tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous cases of HeLPS treated using neurosurgery are listed in Table . Only 6 such cases were treated with MVD; symptoms were relieved in all cases although transient vagus nerve palsy occurred in 3 cases. [4][5][6][7][8] Preoperatively, 4 of the 6 reported patients were taken to the emergency department and 2 were admitted to the intensive care unit. One patient was intubated for respiratory distress and stridor; the other required a tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Only 6 such cases were treated with MVD; symptoms were relieved in all cases although transient vagus nerve palsy occurred in 3 cases. 4-8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Honey et al proposed neurovascular compression of the vagus nerve rootlets identified on magnetic resonance imaging [ 21 ] as a potential cause of vagal dysfunction presenting in the larynx with sensory symptoms of abnormal throat sensations [ 22 ] associated with motor symptoms of laryngospasm/choking, neurogenic cough or intermittent stridor [ 23 ].…”
Section: Introductionmentioning
confidence: 99%